The Atlantic world
1 online resource (xxii, 704 pages)
Keywords: "As the meeting point between Europe, colonial America, and Africa, the history of the Atlantic world is a constantly shifting arena, but one which has been a focus of huge and vibrant debate for many years. In over thirty chapters, all written by experts in the field, The Atlantic World takes up these debates and gathers together key, original scholarship to provide an authoritative survey of this increasingly popular area of world history"--Provided by publisher.